Interview with Rajmil Fischman (1956) by Marino Martínez Espinoza - Martínez Espinoza, Marino (2024)
Interview with Rajmil Fischman (1956) by journalist Marino Martínez Espinoza, where various topics related to Fischman's composition process are addressed, like the influence of new experiences and diverse cultural contexts in his creative universe, nationalism in his music, the transformation of electronic music, the relationship between poetry and music, among others.